Proceedings of the 17th LACCEI International Multi-Conference for Engineering, Education, and Technology: “Industry, Innovation 2019
DOI: 10.18687/laccei2019.1.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Optimized plant distribution and 5S model that allows SMEs to increase productivity in textiles

Abstract: In Peru, the Textile sector generates between 350 and 400 thousand direct jobs, representing 1.9% of Gross domestic product (GDP) and just over 10% of manufacturing. SMEs are characterized by being formed by family businesses, low levels of investment in new technologies and limited financial resources. This context has made SMEs are delayed compared to large companies in implementing Lean Manufacturing. Manufacturing textile companies that have problems with low productivity, excessive use of physical space, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 6 publications
0
14
0
2
Order By: Relevance
“…The development of this method provides an optimal distribution of spaces to establish a better environment for the movement of materials, storage, and all operational activities. Furthermore, it improves the distance flow of the complete system between machines, workstations and material storage places [25] [7]. In this sense, it generates improvements through the reduction of distances and lost times due to an incorrect plant layout.…”
Section: The Slp Methodsmentioning
confidence: 99%
“…The development of this method provides an optimal distribution of spaces to establish a better environment for the movement of materials, storage, and all operational activities. Furthermore, it improves the distance flow of the complete system between machines, workstations and material storage places [25] [7]. In this sense, it generates improvements through the reduction of distances and lost times due to an incorrect plant layout.…”
Section: The Slp Methodsmentioning
confidence: 99%
“…Philosophy that creates and maintains a more efficient and productive space [9]. The socalled 5s is a tool belonging to the Lean Manufacturing section and is one of the first to be studied and applied within an SME such as in the manufacturing, textile or beverage industry to implement a total management system [10]. Previous studies mention that one of the problems they face is the high production times and for this, they propose several Lean Manufacturing tools and among them is the 5S to achieve process improvement in a bottling water company [11].…”
Section: S'mentioning
confidence: 99%
“…Furthermore, it was found that the use of simulation tools supports the viability of Lean improvements in SMEs. It was demonstrated [82] that layout changing and 5S reduce waste in the production process. Simulation software to test and validate the improvements before the implementation is most effective in reducing the total cycle time.…”
Section: How Can Digitalization Support Lean Implementation In Smes?mentioning
confidence: 99%